2017
DOI: 10.1175/jcli-d-16-0437.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Sea Ice Thickness Initialization on Seasonal Arctic Sea Ice Predictions

Abstract: A promising means for increasing skill of seasonal predictions of Arctic sea ice is improving sea ice thickness (SIT) initial conditions; however, sparse SIT observations limit this potential. Using the Canadian Climate Model, version 3 (CanCM3), three statistical models designed to estimate SIT fields for initialization in a real-time forecasting system are applied to initialize sea ice hindcasts over 1981–2012. Hindcast skill is assessed relative to two benchmark SIT initialization methods (SIT-IMs): a clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…By performing multiple hindcast simulations using a fully coupled GCM, Bushuk et al (2017a) provide the first extensive analysis of regional Arctic SIE prediction skill, highlighting both key physical mechanisms underlying skillful predictions and assessing forecast skill in each region. Consistent with previous work that relates summer sea ice prediction skill to sea ice thickness (Blanchard-Wrigglesworth, Armour, et al, 2011;Chevallier & Salas-Mélia, 2012;Collow et al, 2015;Dirkson et al, 2017), Bushuk et al (2017a) demonstrate that skillful regional predictions of summertime sea ice depend on initialization of sea ice thickness, while wintertime predictions hinge on initialization of subsurface ocean temperatures.…”
Section: Introductionsupporting
confidence: 83%
“…By performing multiple hindcast simulations using a fully coupled GCM, Bushuk et al (2017a) provide the first extensive analysis of regional Arctic SIE prediction skill, highlighting both key physical mechanisms underlying skillful predictions and assessing forecast skill in each region. Consistent with previous work that relates summer sea ice prediction skill to sea ice thickness (Blanchard-Wrigglesworth, Armour, et al, 2011;Chevallier & Salas-Mélia, 2012;Collow et al, 2015;Dirkson et al, 2017), Bushuk et al (2017a) demonstrate that skillful regional predictions of summertime sea ice depend on initialization of sea ice thickness, while wintertime predictions hinge on initialization of subsurface ocean temperatures.…”
Section: Introductionsupporting
confidence: 83%
“…For example, sea ice concentration and surface temperature in spring are introduced into a multiple linear regression model to forecast the minimum Arctic sea ice extent (Drobot, 2007;Drobot et al, 2006). Some studies suggested that accurate sea ice thickness can increase forecast skill 2 months ahead (Day et al, 2014;Dirkson et al, 2017). Recently, the spring melt pond fraction has been employed to improve the skill of forecasting September sea ice extent (Liu et al, 2015;Schröder et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The monthly-mean ice thickness and ice concentration gridded data products of PIOMAS were also used for spatial comparison (Dirkson et al, 2016).…”
Section: Piomas and Siiv3 Data Productsmentioning
confidence: 99%